Optimization Of Micro, Small and Medium Enterprise Financial Management Through Android-Based Zazan Mobile Application for Efficiency of Digital Economy Sustainability - Yoga, Titan Parama; Setiana, Elia; Hamzah, Encep; Budiman, Budiman; Sarifiyono, Aggi Panigoro (Jurnal Computech & Bisnis (e-journal), 2024)
In order to sustain and grow a firm, financial management is essential. This procedure is essential for obtaining profit and loss data, preventing employee and business partner fraud, and separating personal and business funds to determine the company's financial situation accurately. Informal MSME actors multitask and operate as small business owners, entrepreneurs, and managers of all business issues. So, there is not enough time to document the financials of a corporation. Making financial records requires basic knowledge, which makes the work feel challenging, intricate, and time-consuming. One way to address this issue is making the Android mobile application "Zazan" to assist in managing the finances of medium-sized, tiny, and microbusinesses. A descriptive strategy was used to gather the data required for this investigation. An integrated application that could record business activity transactions, record business activity schedules, and connect with customers was required, as determined by the analysis and implementation findings. Furthermore, clients can quickly learn more about business players by accessing location information. Interaction between customers and business transaction activities facilitates the automation of business activity recording, enabling the application to complete financial recording. Entrepreneurs will find it easier to manage their financial spending with the help of the company's financial reports. Having employee and multi-store functionalities would be preferable because business actors occasionally have multiple business branches and employees. The implications of this research extend beyond merely providing a tool for financial management; they highlight the necessity of accessible financial solutions for MSMEs. By bridging the gap in financial literacy and time constraints, the "Zazan" application not only empowers business owners to maintain accurate financial records but also fosters better decision-making and strategic planning. This can lead to enhanced business performance, improved relationships with stakeholders, and ultimately, sustainable growth in the competitive market landscape.